Considerations for the use of anesthesia in patients undergoing tricyclic antidepressant treatment - Iván Hamyd Salazar Carrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Patients undergoing tricyclic antidepressant treatment given anesthesia have experienced the hypotensive effects of both drugs. Traditionally it was recommended to suspend these drugs until two weeks before surgery; however, it is currently proposed that they should not be discontinued, since despite the side effects and possible interactions with anesthetic agents, cases of suicide have been described after its suspension. For these reasons, this bibliographic review was carried out aimed at updating considerations for the use of anesthesia in patients undergoing treatment with tricyclic antidepressants. It was observed that in the developed studies it is suggested that surgical technique individualization, use of pre-anesthetic medication, reduction of sympathetic stimulation and an adequate control of postoperative pain, will result in a decrease in the deleterious effects produced by the association of tricyclic antidepressants and anesthetic agents.